Corticosteroid-Binding Globulin: Structure-Function Implications from Species Differences - Gardill, Bernd; Vogl, Michael R.; Lin, Hai-Yan; Hammond, Geoffrey L.; Muller, Yves (PLoS ONE, 2012)

Design of an allosterically modulated doxycycline and doxorubicin drug-binding protein. - Schmidt, Karin; Gardill, Bernd; Kern, Alina; Kirchweger, Peter; Börsch, Michael; Muller, Yves (Proceedings of the National Academy of Sciences of the United States of America, 2018)
The allosteric interplay between distant functional sites present in a single protein provides for one of the most important regulatory mechanisms in biological systems. While the design of ligand-binding sites into proteins remains challenging, this holds even truer for the coupling of a newly engineered binding site to an allosteric mechanism that regulates the ligand affinity. Here it is shown how computational design algorithms enabled the introduction of doxycycline- and doxorubicin-binding sites into the serine proteinase inhibitor (serpin) family member α1-antichymotrypsin. Further engineering allowed exploitation of the proteinase-triggered serpin-typical S-to-R transition to modulate the ligand affinities. These design variants follow strategies observed in naturally occurring plasma globulins that allow for the targeted delivery of hormones in the blood. By analogy, we propose that the variants described in the present study could be further developed to allow for the delivery of the antibiotic doxycycline and the anticancer compound doxorubicin to tissues/locations that express specific proteinases, such as bacterial infection sites or tumor cells secreting matrix metalloproteinases.

NewBG: A surrogate corticosteroid-binding globulin with an unprecedentedly high ligand release efficacy - Gardill, Bernd; Schmidt, Karin; Muller, Yves (Journal of Structural Biology, 2019)
The introduction of ligand-binding sites into proteins and the engineering of molecular allosteric coupling pathways are topical issues in protein design. Here, we show that these issues can be addressed concurrently, using the serpin human α1-antichymotrypsin (ACT) as a model. We have introduced up to 15 amino acid substitutions into ACT, converting it into a surrogate corticosteroid-binding globulin (CBG), thereby creating a new binding globulin (NewBG). Human CBG and ACT share 46% sequence identity, and CBG served as the blue-print for our design, which was guided by side-chain-packing calculations, ITC measurements and crystal structure determinations. Upon transfer of ligand-interacting residues from CBG to ACT and mutation of specific second shell residues, a NewBG variant was obtained, which binds cortisol with 1.5 µM affinity. This novel serpin (NewBG-III) binds cortisol with a 33-fold lower affinity than CBG, but shares a similar ligand-binding profile and binding mode when probed with different steroid ligands and site-directed mutagenesis. An additional substitution, i.e. A349R, created NewBG-III-allo, which introduced an allosteric coupling between ligand binding and the serpin-like S-to-R transition in ACT. In NewBG-III-allo, the proteinase-triggered S-to-R transition leads to a greater than 200-fold reduction in ligand affinity, and crystal structures suggest that this is mediated by the L55V and A349R substitutions. This reduction significantly exceeds the 10-fold reduction in binding affinity observed in human CBG.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Allostery; Computational protein design; Crystal structure; Ligand-binding site design; Serpin